2021
DOI: 10.3390/agriculture11100991
|View full text |Cite
|
Sign up to set email alerts
|

‘Helete Güneşi’, a New Walnut Cultivar with Late Leafing, Early Harvest Date, and Superior Nut Traits

Abstract: ‘Helete Güneşi’ was selected among different genotypes obtained from crossing ‘Maraş 18’ × ‘Chandler’ in Turkey. The present study compares phenological and pomological traits of ‘Helete Güneşi’ with those of its parents so as to scale their performances. ‘Helete Güneşi’ staged leaf out on 22 April, whereas its parents, ‘Chandler’ and ‘Maraş 18’, did on 20 and 12 April, respectively. The harvest date of ‘Helete Güneşi’ was as early as 17 September, whereas ‘Chandler’ and ‘Maraş 18’ began to be harvested on 5 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The Walnut (Juglans regia L.) is one of the oldest cultivated fruit species in the world [1]. The kernels have excellent nutritional and therapeutic value due to their high content of unsaturated fatty acids [2] and abundant amino acids and minerals [3,4]. In postharvest and processing, compared to other operations (e.g., cleaning, drying, storing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Walnut (Juglans regia L.) is one of the oldest cultivated fruit species in the world [1]. The kernels have excellent nutritional and therapeutic value due to their high content of unsaturated fatty acids [2] and abundant amino acids and minerals [3,4]. In postharvest and processing, compared to other operations (e.g., cleaning, drying, storing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…9, 13, 32, 33, 72, 77, 78, 82, 83, 86, 92, and 98) were identified and are recommended for cultivation in orchards. Sütyemez et al [ 32 ] introduced ‘Helete Güneşi’, as a new walnut cultivar with late leafing, early harvest date, and superior nut traits in Turkey. Also, Bükücü [ 33 ] studied 74 F1 progenies obtained from ‘Chandler’ × ‘Sutyemez 1’ walnuts in Turkey and reported that the progenies studied are a valuable gene pool for walnut breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…Walnuts are one of the four major nuts globally, and the internal kernel is rich in nutrients (Sütyemez et al, 2021). From 2010 to 2019, there was a noticeable rise in walnut production, with an increase of approximately 1.17 million tons.…”
Section: Introductionmentioning
confidence: 99%